Location and cloning of the ketal pyruvate transferase gene of Xanthomonas campestris - Marzocca, M.P. (1991)
Genes required for xanthan polysaccharide synthesis (xps) are clustered in a DNA region of 13.5 kb in the chromosome of Xanthomonas campestris. Plasmid pCHC3 containing a 12.4-kb insert of xps genes has been suggested to include a gene involved in the pyruvylation of xanthan gum (N. E. Harding, J. M. Cleary, D. K. Cabanas, I. G. Rosen, and K. S. Kang, J. Bacteriol. 169:2854-2861, 1987). An essential step toward understanding the biosynthesis of xanthan gum and to enable genetic manipulation of xanthan structure is the determination of the biochemical function encoded by the xps genes. On the basis of biochemical characterization of an X. campestris mutant which produces pyruvate-free xanthan gum, complementation studies, and heterologous expression, we have identified the gene coding for the ketal pyruvate transferase (kpt) enzyme. This gene was located on a 1.4-kb BamHI fragment of pCHC3 and cloned in the broad-host-range cloning vector pRK404. An X. campestris kpt mutant was constructed by mini-Mu(Tet(r)) mutagenesis of the cloned gene and then by recombination of the mutation into the chromosome of the wild-type strain.